Comparing the epigenetic landscape in myonuclei purified with a PCM1 antibody from a fast/glycolytic and a slow/oxidative muscle - Mads Bengtsen (Public Library of Science (PLoS), 2021)
Muscle cells have different phenotypes adapted to different usage, and can be grossly divided into fast/glycolytic and slow/oxidative types. While most muscles contain a mixture of such fiber types, we aimed at providing a genome-wide analysis of the epigenetic landscape by ChIP-Seq in two muscle extremes, the fast/glycolytic extensor digitorum longus (EDL) and slow/oxidative soleus muscles. Muscle is a heterogeneous tissue where up to 60% of the nuclei can be of a different origin. Since cellular homogeneity is critical in epigenome-wide association studies we developed a new method for purifying skeletal muscle nuclei from whole tissue, based on the nuclear envelope protein Pericentriolar material 1 (PCM1) being a specific marker for myonuclei. Using antibody labelling and a magnetic-assisted sorting approach, we were able to sort out myonuclei with 95% purity in muscles from mice, rats and humans. The sorting eliminated influence from the other cell types in the tissue and improved the myo-specific signal. A genome-wide comparison of the epigenetic landscape in EDL and soleus reflected the differences in the functional properties of the two muscles, and revealed distinct regulatory programs involving distal enhancers, including a glycolytic super-enhancer in the EDL. The two muscles were also regulated by different sets of transcription factors; e.g. in soleus, binding sites for MEF2C, NFATC2 and PPARA were enriched, while in EDL MYOD1 and SIX1 binding sites were found to be overrepresented. In addition, more novel transcription factors for muscle regulation such as members of the MAF family, ZFX and ZBTB14 were identified. Author summary Complex tissues like skeletal muscle contain a variety of cells which confound the analysis of each cell type when based on homogenates, thus only about half of the cell nuclei in muscles reside inside the muscle cells. We here describe a labelling and sorting technique that allowed us to study the epigenetic landscape in purified muscle cell nuclei leaving the other cell types out. Differences between a fast/glycolytic and a slow/oxidative muscle were studied. While all skeletal muscle fibers have a similar make up and basic function, they differ in their physiology and the way they are used. Thus, some fibers are fast contracting but fatigable, and are used for short lasting explosive tasks such as sprinting. Other fibers are slow and are used for more prolonged tasks such as standing or long distance running. Since fiber type correlate with metabolic profile these features can also be related to metabolic diseases. We here show that the epigenetic landscape differed in gene loci corresponding to the differences in functional properties, and revealed that the two types are enriched in different gene regulatory networks. Exercise can alter muscle phenotype, and the epigenetic landscape might be related to how plastic different properties are.